Effect of harvesting and processing of stinging nettle on the antioxidant capacity of its infusions - Česlová, Lenka; Šilarová, Petra; Fischer, Jan (University of Pardubice, 2016)
The antioxidant properties of different matrices can be determined using various methods. In this work, two spectrophotometric methods based on the scavenging activity of the radicals DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2’- azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) were used together with a spectrophotometric method based on the ferric reduction power of phenolic compounds. The results obtained using all three methods were compared and discussed for infusions prepared from different parts of stinging nettle (Urtica dioica L.). The relation with the time of harvest and location of grow were also examined. Finally, the antioxidant capacity of all the studied nettle infusions were correlated with the total phenolic content determined using Folin–Ciocalteu reagent.